Alterations to oxidative stress markers in dogs after a short-term stress during transport - Ferreira, Chayanne S. [UNESP]; Vasconcellos, Ricardo S.; Pedreira, Raquel S. [UNESP]; Silva, Flavio L. [UNESP]; Sá, Fabiano C. [UNESP]; Kroll, Fernanda S A [UNESP]; Maria, Ana P J [UNESP]; Venturini, Katiani S. [UNESP]; Carciofi, Aulus C. [UNESP] (Journal of Nutritional Science, 2014)
While methods to evaluate antioxidant capacity in animals exist, one problem with the models is induction of oxidative stress. It is necessary to promote a great enough challenge to induce measurable alterations to oxidative parameters while ensuring the protocol is compatible with animal welfare. The aim of the present study was to evaluate caged transport as a viable short-term stress that would significantly affect oxidative parameters. Twenty adult Beagle dogs, maintained on the same diet for 60 d prior to the transport, were included in the study. To simulate the stress, the dogs were housed in pairs in transport cages (1·0 m × 1·0 m × 1·5 m), placed on a truck coupled to a trailer and transported for a period of 15 min. Blood collection was performed immediately before and again 3 h after the transportation to evaluate oxidative parameters in blood serum, including thiobarbituric acid reactive substances (TBARS), total antioxidant capacity (TAC), sequestration activity of the radical 2,2-diphenyl-1-picryl-hydrazyl (DPPH•), protein carbonylation (PC), total sulfhydryl groups (SH), alpha-tocopherol (αToc) and retinol (Ret). PC, SH and αToc were not significantly changed in the study; however, TBARS, TAC and DPPH increased, whereas Ret decreased after the transport. Although the lack of a control group of dogs not submitted to transport is a limitation to be considered, we conclude that the transport model is effective in inducing an antioxidant response in dogs and relevant blood parameters show sensitivity to this proposed model.
Keywords: Alpha-tocopherol; Antioxidants; Canine nutrition; Dpph, 2,2-diphenyl-1-picryl-hydrazyl; Lipoperoxidation; Pc, protein carbonilation; Ros, reactive oxygen species; Ret, retinol; Sh, total sulfhydryl groups; Tac, total antioxidant capacity; Tbars, thiobarbituric acid reactive substances; Thiobarbituric acid; Αtoc, α-tocopherol